2019
DOI: 10.1155/2019/1643804
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Associated with Ethical Kampo Formulations: Analysis of the Domestic Adverse-Event Data Reports of the Ministry of Health, Labor, and Welfare in Japan

Abstract: Objectives. Traditional Japanese Kampo medicines have been integrated into the Japanese national health-care system. In Japan, the Ministry of Health, Labor, and Welfare’s website discloses adverse drug-event data that have been obtained from medical personnel reports investigated by the Pharmaceutical and Medical Devices Agency. Using these data, we investigated adverse events associated with ethical Kampo formulations. Methods. Reports of adverse events associated with ethical Kampo formulations from the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 49 publications
(63 reference statements)
0
31
0
Order By: Relevance
“…Larger cohorts and greater numbers now support this crucial relationship. In a Japanese cohort of 73 patients, pneumonitis development occurred within 3 months of commencing traditional medicine in the majority of patients [3], while a large report from the Japanese Ministry of Health, Labor and Welfare, described more than 1000 cases of lung injury secondary to traditional medications, the overwhelming majority of which (852 reports) were described as 'interstitial lung disease [4].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Larger cohorts and greater numbers now support this crucial relationship. In a Japanese cohort of 73 patients, pneumonitis development occurred within 3 months of commencing traditional medicine in the majority of patients [3], while a large report from the Japanese Ministry of Health, Labor and Welfare, described more than 1000 cases of lung injury secondary to traditional medications, the overwhelming majority of which (852 reports) were described as 'interstitial lung disease [4].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…TJ-14 contains Coptidis Rhizoma and Glycyrrhizae Radix, which have been shown to induce side effects such as pseudoaldosteronism and herbal medicine-induced pneumonitis. 14,15 One study reported that TJ-14 may have been associated with liver injury. 9,15 More importantly, however, previous studies that demonstrated side effects used oral administration of TJ-14.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 One study reported that TJ-14 may have been associated with liver injury. 9,15 More importantly, however, previous studies that demonstrated side effects used oral administration of TJ-14. In our study, patients gargled the medication, which is a safer and more effective method of administration for head and neck cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians should note that previous studies have revealed not only clinical usefulness of Kampo medicines to improve several clinical manifestations but also possible adverse effects. A recent review article reports that frequent events caused by Kampo medicines include liver injury (28.2%) followed by lung injury (27.8%), psedoaldosteronism (21.0%), mesenteric phlebosclerosis (5.3%), drug eruption (4.4%), and others (13.3%) [48]. Since the classification of types of adverse reactions; acute, bizarre, chronic, or delayed onset, is applied both in Western drugs as well as Kampo herbs [49], it is important to note that pharmacotoxicity of Kampo herbs can occur at any timing.…”
Section: Adverse Effects Of Kampo Medicinementioning
confidence: 99%